2013
DOI: 10.5152/jarem.2013.17
|View full text |Cite
|
Sign up to set email alerts
|

Our Experience in Percutaneous Endoscopic Gastrostomy

Abstract: ÖZETAmaç: Kritik hastaların bakım ve tedavisi sırasında enteral beslenme, enerji ihtiyacının karşılanması, vücut direncinin korunması, gastrointestinal sistem (GİS) florasının korunması ve translokasyonların önlenmesi açısından çok önemlidir. Bu çalışmadaki amacımız; hastanemizde PEG takılması planlanan hastaların PEG takılma endikasyonlarını, işlem sonrası komplikasyonlarını ve takipleri ile ilgili verileri sunmaktır.Yöntemler: Çalışmamızda Abant İzzet Baysal Üniversitesi Tıp Fakültesi Genel Cerrahi Anabilim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Dysphagia due to neurological disorders is among the main reasons for the need for PEG (8,9). In our country, in a study conducted by Kartal et al (10) in Erzurum, the need for PEG due to neurologic causes was found to be 76.4%, while Şit et al (11) found this value to be 60% in Bolu region. In accordance with the literature, 84.5% of our patients needed PEG due to swallowing problems due to neurological causes.…”
Section: Discussionmentioning
confidence: 70%
“…Dysphagia due to neurological disorders is among the main reasons for the need for PEG (8,9). In our country, in a study conducted by Kartal et al (10) in Erzurum, the need for PEG due to neurologic causes was found to be 76.4%, while Şit et al (11) found this value to be 60% in Bolu region. In accordance with the literature, 84.5% of our patients needed PEG due to swallowing problems due to neurological causes.…”
Section: Discussionmentioning
confidence: 70%